(untitled) (Global Journal of Science Frontier Research, 2015)
Ocimum sanctum is a sacred herb of India is also known as ’Tulsi’ or ’Holy Basil’. There are several medicinal properties attributed to leaf, bark, root as well as seeds of O. sanctum. This holy plant is used in the present investigation to study its angiogenic efficiency. The effect of methanolic extract of O. sanctum leaves was studied by using chick chorioallantoic membrane (CAM) assay in ovo. The angiogenesis was studied after 48 hrs, 72 hrs and 96 hrs treatment of on chick CAM after day 6. The CAM was studied morphometrically and histologically. There was highly significant decrease in number of secondary and tertiary blood vessels as well as in total CAM area.